Excerpted from The Days and Nights of the Lotus Trio - Ives, Michael (Current Musicology, 2013)
The following texts are drawn from a series of vignettes concerning a hapless, over–educated trio of jazz musicians who ply their trade in an unnamed city during an historical period best described as the “eternal jazz present.” In every sense lotus eaters, this band of ineffectual brothers, however competent, even occasionally brilliant as musicians, are forever hampered by their own fin–de–siècle fetishisms. They are proof of the obstacles an over–developed connoisseurship places in the way of the pragmatic business of getting gigs. A fondness for cannabis and an addiction to refined banter jeopardize nearly all their ambitions, save their often acidulous judgments of their peers. The prose itself—however informed by the absurd sophistications of Ronald Firbank (whose dialogic exchanges call to mind the snare drum accents of Roy Haynes) or the underground classic, A Nest of Ninnies (Ashbery–Schuyler)—means to serve as something like a parodic homage to that dandy of jazz writing, Whitney Balliett.